Avaliação da reposição hormonal sobre o tecido ósseo alveolar de ratas ovariectomizadas com doença periodontal induzida - Boamorte, Carolina de Cassia (2016)
The ratio of osteoporosis in postmenopausal women is controversial, but may be a risk factor for periodontal disease, as well as having a direct or indirect role in bone due to estrogen action, since this can inhibit production of proinflammatory cytokines -inflammatory such as TNF-alpha and IL-6 that favor bone resorption. One of the alternatives in hormone replacement therapy is the isoflavone, a phyto-hormone that has established itself as replacement therapy for having a similar action to estrogen, but with protective effects against cancers, osteoporosis, among others. The objective was to evaluate the effect of isoflavone on alveolar bone of ovariectomized rats with induced periodontitis. Sixty (60) Female rats with 8 weeks of age were randomly divided into 6 groups: 1) control group (CON); 2) Bandage Group (LIG); 3) Group Ovariectomy (OVX); 4) Ovariectomia and Phytoestrogen group (OVX + FIT); 5) Ovariectomia and ligature group (OVX + LIG); 6) Ovariectomia Group, Phytoestrogen and Ligation (OVX + FIT + LIG) .All the animals received standard diet and water at will. After 70 days of life, the animals were anesthetized (xylazine 10 mg / kg and ketamine 75 mg / kg) and were placed in proper operating table, which allowed the maintenance of the mouth opening of the rats facilitating access to the teeth of the posterior region jaw. With the aid of a modified forceps and an explorer, it was placed a cotton yarn number 40 around the mandibular first molar right and left. After this procedure, after 79 days of life, the rats were submitted to anesthesia and ovariectomy surgery to mimic the absence of female sex hormones of menopause in women. Ligation served as irritating gums for 30 days and favored the accumulation of plaque, while hormone replacement therapy (isoflavone) was held for 21 days (0.25 g / kg / day sc) in the above-mentioned groups. At 100 days of life, the rats were euthanized. Macroscopic, microscopic and X-ray analyzes were performed with the left and right jaws of each rat as well with samples of gingival tissue to assess the periodontal tissues and their effects induced by hormone replacement. As a result of analysis, it was observed that the groups of phytoestrogen showed less bone loss than the groups that received no therapy isoflavone (p <0.05) and the treated groups had a higher phytoestrogen osteoblasts and osteocytes osteoclasts and lower than the groups not receiving hormone replacement therapy (p <0.05). Therefore, the isoflavone may confer a protective effect on bone loss in periodontal disease progression, compounded by osteoporosis.